Individual Differences in Pain Catastrophizing and Regional Gray Matter Volume Among Community-dwelling Adults With Chronic Pain: A Voxel-based Morphology Study. Issue 5 (21st May 2023) - Liu, Shuyang; You, BeiBei; Zhang, Xin; Shaw, Amy; Chen, Hong; Jackson, Todd
Abstract : Objectives: Elevations in pain catastrophizing (PC) are associated with more severe pain, emotional distress, and impairment within samples with chronic pain. However, brain structure correlates underlying individual differences in PC are not well understood and predict more severe pain and impairment within samples with chronic pain. This study assessed links between regional gray matter volume (GMV) and individual differences in PC within a large mixed chronic pain sample. Materials and Methods: Chinese adult community dwellers with chronic pain of at least 3 months duration (101 women and 59 men) completed self-report measures of background characteristics, pain severity, depression, and a widely validated PC questionnaire as well as a structural magnetic resonance imagining scan featuring voxel-based morphology to assess regional GMV correlates of PC. Results: After controlling for demographic correlates of PC, pain severity, and depression, higher PC scores had a significant, unique association with lower GMV levels in the inferior temporal area of the right fusiform gyrus, a region previously implicated in emotion regulation. Discussion: GMV deficits, particularly in right temporal-occipital emotion regulation regions, correspond to high levels of PC among individuals with chronic pain.